E-Library Interaktif dengan SLiMS Bulian Menggunakan Metode RAD - arief Ichwani (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2022)
The use of technology in various fields has developed very quickly and has become a necessity in supporting the services of an organization or company. Educational institutions are one of the sectors that are guided in the learning process using Information and Communication Technology (ICT). Education, especially libraries, is one of the fields that uses high ICT, namely the digitalization of libraries or often e-libraries in order to realize quality education and ICT competitiveness in the world of education. As for the e-library in educational institutions, one of the schools is a source of information or reference for students, to increase students' reading interest, as well as to increase students' knowledge and competence. This makes the e-library has a very important role and must be developed to meet these needs such as developing an interactive and interesting e-library. The methods used for data collection are observations to the school library, interviews with library managers, and literature studies to deepen problem understanding. The software development method used is Rapid Application Development (RAD) by utilizing the Unified Modeling Language (UML) to design the system design developed. The results of this study are the existence of a complete e-library and an attractive application design and forum feature that makes the e-library interactive so that it can encourage the level of visits and literacy culture for students. The e-library has been carried out through black box testing and System Usability Test (SUS) with acceptable results.